Enhancing forecast accuracy for lumpy demand using hybrid machine learning model - Le, Thi Chau Giang (Nanyang Technological University, 2025)
Demand forecasting is a critical aspect of supply chain management, underpinning decision-making processes that span from strategic operations planning to daily workload management. Given its importance, substantial research efforts have been devoted to developing and optimizing forecasting tools to enhance supply chain efficiency.